Pengaruh Citra Merek, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Sepatu Pada Toko Lana Sneakers - Ajhari, Ana; Purnama, Ita; Ernawati, Sri (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
The purpose of this study is to find out and explain the influence of brand image, product quality, and price on shoe purchase decisions at Lana Sneakers store. The data of this study is the consumer of the lana sneaker store, with samples taken using puposive sampling so that a sample of 96 respondents was obtained. The method used in this study is descriptive with a quantitative approach. The data collection method in this study is the distribution of questionnaires through google forms in the form of questions to respondents. Multiple linear regression analysis is used as the analysis method in this study. The results of the study explained that brand image, product quality, and price have a significant influence on purchasing decisions, with an influence of 47.4%.